1976
DOI: 10.1152/ajplegacy.1976.231.3.954
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and pathophysiological changes in chronic two-kidney hypertension in the dog

Abstract: Unilateral renal artery plication in dogs reduced renal blood flow by 80% and produced a sustained elevation in arterial pressure whereas plasma renin activity increased for only 4 days. Sodium was retained for 3 days after plication, but this response is similar to that after a sham operation. Of seven dogs studied chronically, elevated arterial pressure was sustained for 27 days or longer in six animals. In three dogs hypertension continued for 2 mo before collateral vessels developed and arterial pressure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…1979b) and other investigators have also reported that several progressive adjustments of the constrictive device were often necessary to reliably achieve systemic hypertension (e.g. Lupu, Maxwell, Kaufman & White, 1972;Tagawa, Gutmann, Haber, Miller, Samuels & Barger, 1974;Ayers et al 1974;Watkins, Davis, Hanson, Lohmeier & Freeman, 1976). The present experiments may point to another method; namely production of a moderate stenosis gradient while the kidney is vasoconstricted pharmacologically.…”
Section: Discussionmentioning
confidence: 97%
“…1979b) and other investigators have also reported that several progressive adjustments of the constrictive device were often necessary to reliably achieve systemic hypertension (e.g. Lupu, Maxwell, Kaufman & White, 1972;Tagawa, Gutmann, Haber, Miller, Samuels & Barger, 1974;Ayers et al 1974;Watkins, Davis, Hanson, Lohmeier & Freeman, 1976). The present experiments may point to another method; namely production of a moderate stenosis gradient while the kidney is vasoconstricted pharmacologically.…”
Section: Discussionmentioning
confidence: 97%
“…27 * 28 Though this is the case in acute animal models, it is less clearly so in humans and animals with chronic renal artery lesions. 29 …”
Section: Discussionmentioning
confidence: 99%
“…As reported by DAVIS (1977), the response to renal artery stenosis greatly differs between dogs and rats. In fact, in rats, constriction of one renal artery produces chronic hypertension and maintains elevation of PRA during the chronic stage (DAVIS, 1977), whereas in the dogs with chronic two-kidney hypertension, PRA is normal (WATKINS et al, 1976).…”
Section: Discussionmentioning
confidence: 99%